Integrable generalizations of oscillator and Coulomb systems via action–angle variables; Physics Letters A; Vol. 376, iss. 5 - Akopyan (Hakobyan) T. S. Tigran Stepanovich; Lechtenfeld O. Olaf; Nersessian A. P. Armen Petrosovich; Saghatelian A.; Yeghikyan V. (2012, 2012)
Title screen